Pressure Drop and Particle Settlement of Gas–Solid Two-Phase Flow in a Pipe - Wenqian Lin; Liang Li; Yelong Wang (Applied Sciences, 2022)
Particle settlement and pressure drop in a gas–solid two-phase flow in a pipe with a circular cross-section are studied at mixture inlet velocities (V) ranging from 1 m/s to 30 m/s, particle volume concentrations (αs) ranging from 1% to 20%, particle mass flows (ms) ranging from 5 t/h to 25 t/h, and particle diameters (dp) ranging from 50 μm to 1000 μm. The momentum equations are based on a two-fluid model and are solved numerically. Some results are validated through comparison with the experimental results. The results showed that the gas and particle velocity distributions are asymmetrical around the center of the pipe and that the maximum velocity point moves up. The distance between the radial position of the maximum velocity and the center line for the gas is larger than that for the particles. The particle motion lags behind that of the gas flow. The particle settlement phenomenon is more serious, and the particle distribution on the cross-section is more inhomogeneous as the V, αs, and ms decrease and as dp increases. It can be divided into three areas according to the pressure changes along the flow direction, and the distinction between the three areas is more obvious as the αs increases. The pressure drop per unit length increases as the V, αs and ms increases and as dp decreases, Finally, the expressions of the settlement index and pressure drop per unit length as functions of V, αs, ms, and dp are derived based on the numerical data.